KARAKTERISTIK PENDERITA STROKE HAEMORAGIK YANG DIRAWAT INAP DI RSUP H. ADAM MALIK MEDAN TAHUN 2012 - berman girsang; drh. Hiswani, MKes; dr. Mhd Makmur Sinaga, MS (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Stroke was a disorder of blood circulation in the brain due to blocked or rupture of blood vessels. Stroke was divided into two parts based on the pathological namely, ischemic and hemorrhagic stroke. Of entire the number of cases of stroke, 80% had ischemic stroke and 20% of stroke hemorrhagic. Stroke was the main cause of death in Indonesia with a proportion of 14.4%. To determine the characteristics of stroke hemorrhagic patients hospitalized, conducted research at RSUP H. Adam Malik Medan with case series design. Population and the sample was 111 people in 2012 which recorded in hospital medical records. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-square test and ANOVA. Proportion based on the highest sociodemographic in the age group 45-59 years 48.6%, men 51.4%, muslim 63.1%, high school / equal 41.4%, 96.4% married status, housewife 41, 4%, and 77.5% outside the city of Medan. Proportion based on the highest treatment status, 73% decreased consciousness, hemiparesis dextra 53.2%, hypertension 78.4%, intracerebral hemorrhage 83.8%, 43.7% cerebral hemifer, 99.1% of conservative measures, long maintainability average 6.37 days, insurance 82.9%, and 64.9% died. There was no significant difference between the average treatment time with the main complaints (p = 0.161), location of the paralysis (p = 0.81), and the site of bleeding (p = 0.085). There was a significant difference between the average treatment time of patients with CT-Scan results (0.024) and the condition while returning (p = 0.000). Patients who have a history of hypertension to perform the routine control and a healthy lifestyle. Medical treatment and maintainability for patients was done intensively to reduce mortality rate. For the medical records department of RSUP H. Adam Malik Medan to complete patient data recording such as ethnicity and location of bleeding.